7(3-4x)-5(2x+8)=0

Simple and best practice solution for 7(3-4x)-5(2x+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3-4x)-5(2x+8)=0 equation:


Simplifying
7(3 + -4x) + -5(2x + 8) = 0
(3 * 7 + -4x * 7) + -5(2x + 8) = 0
(21 + -28x) + -5(2x + 8) = 0

Reorder the terms:
21 + -28x + -5(8 + 2x) = 0
21 + -28x + (8 * -5 + 2x * -5) = 0
21 + -28x + (-40 + -10x) = 0

Reorder the terms:
21 + -40 + -28x + -10x = 0

Combine like terms: 21 + -40 = -19
-19 + -28x + -10x = 0

Combine like terms: -28x + -10x = -38x
-19 + -38x = 0

Solving
-19 + -38x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + -38x = 0 + 19

Combine like terms: -19 + 19 = 0
0 + -38x = 0 + 19
-38x = 0 + 19

Combine like terms: 0 + 19 = 19
-38x = 19

Divide each side by '-38'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 4(6m+3)=-276 | | 6(4+7d)=192 | | 5(2a+8)=40 | | 3(-1a-1)=-33 | | 6(-7b-1)=288 | | 5(2x-3)-3(x-2)=0 | | 2(7k+2)=-52 | | 7(9+6a)=357 | | 6(-3x+2)=-78 | | 2(9+5w)=138 | | 2(2-5b)=104 | | 3(5b+1)=18 | | 6(-1m+5)=-36 | | 4(4+2t)=80 | | 2(-1x-7)=-28 | | (5x+3)-(4x-9)=0 | | 7(2-5t)=14 | | 6(4+3m)=150 | | 6(-5-3m)=42 | | 6(2+k)=66 | | 6(3t+5)=246 | | 3(2a-9)=3 | | 2(-6m+9)=126 | | 2(5k+7)=74 | | 6(9-2n)=30 | | 2(-8-5t)=-46 | | 2(5+6k)=118 | | 5(5+2m)=105 | | 7(6k+8)=14 | | 2(4k+5)=58 | | 7(-4x+3)=329 | | 6(-5m-3)=-318 |

Equations solver categories